Time to Initiation of Renal Replacement Therapy Among Critically Ill Patients With Acute Kidney Injury: A Current Systematic Review and Meta-Analysis - Thummaporn Naorungroj (2022)
OBJECTIVES: The optimal time to initiate renal replacement therapy in critically ill patients with acute kidney injury is controversial. We investigated the effect of such earlier versus later initiation of renal replacement therapy on the primary outcome of 28-day mortality and other patient-centered secondary outcomes. DESIGN: We searched MEDLINE (via PubMed), EMBASE, and Cochrane databases to July 17, 2020, and included randomized controlled trials comparing earlier versus later renal replacement therapy. SETTING: Multiple centers involved in eight trials. PATIENTS: Total of 4,588 trial participants. Intervention: Two independents investigators screened and extracted data using a predefined form. We selected randomized controlled trials in critically ill adult patients with acute kidney injury and compared of earlier versus later initiation of renal replacement therapy regardless of modality. MEASUREMENTS AND MAIN RESULTS: Overall, 28-day mortality was similar between earlier and later renal replacement therapy initiation (38.43% vs 38.06%, respectively; risk ratio, 1.01; [95% CI, 0.94-1.09]; I2= 0%). Earlier renal replacement therapy, however, shortened hospital length of stay (mean difference, -2.14 d; [95% CI, -4.13 to -0.14]) and ICU length of stay (mean difference, -1.18 d; [95% CI, -1.95 to -0.42]). In contrast, later renal replacement therapy decreased the use of renal replacement therapy (relative risk, 0.69; [95% CI, 0.58-0.82]) and lowered the risk of catheter-related blood stream infection (risk ratio, 0.50, [95% CI, 0.29-0.86). Among survivors, renal replacement therapy dependence at day 28 was similar between earlier and later renal replacement therapy initiation (risk ratio, 0.98; [95% CI, 0.66-1.40]). CONCLUSIONS: Earlier or later initiation of renal replacement therapy did not affect mortality. However, earlier renal replacement therapy was associated with significantly shorter ICU and hospital length of stay, whereas later renal replacement therapy was associated with decreased use of renal replacement therapy and decreased risk of catheter-related blood stream infection. These findings can be used to guide the management of critically ill patients with acute kidney injury.